1994
DOI: 10.1007/bf02354036
|View full text |Cite
|
Sign up to set email alerts
|

Revenue diversification among non-profits

Abstract: Although the non-profit literature has grown substantially, the issue of how revenue diversification affects non-profits has not been fully explored. This paper presents several disciplinary perspectives regarding the financing of non-profits, what determines their ability to diversify, and the consequent effects on their behaviour. It first develops an index for measuring revenue diversification and applies it to a national sample of charitable non-profits. The results indicate that, while the perception that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
173
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(200 citation statements)
references
References 12 publications
6
173
3
Order By: Relevance
“…The test produces a significant F-statistic, affirming differences between the samples used in previous studies and our 34 Although we would have expected debt to have a stronger association with accounting and audit fees, we note that debt is insignificant in the results presented by Beattie et al (2001). 35 This finding is also consistent with research that emphasizes the benefits of nonprofit revenue portfolio strategy (Kearns 2007;Froelich 1999;Chang and Tuckman 1994). 36 We expected an inverse association between INV_INC and LAFEES for all organizations in our sample.…”
Section: Primary Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The test produces a significant F-statistic, affirming differences between the samples used in previous studies and our 34 Although we would have expected debt to have a stronger association with accounting and audit fees, we note that debt is insignificant in the results presented by Beattie et al (2001). 35 This finding is also consistent with research that emphasizes the benefits of nonprofit revenue portfolio strategy (Kearns 2007;Froelich 1999;Chang and Tuckman 1994). 36 We expected an inverse association between INV_INC and LAFEES for all organizations in our sample.…”
Section: Primary Resultssupporting
confidence: 80%
“…Fundamentally, a program ratio that would otherwise be preferable (a percentage that nears 100 percent) may 21 In addition, the nonprofit literature emphasizes the importance of revenue diversification in this setting, giving us further support for disaggregating contributions into its three components. For comprehensive discussions of nonprofit revenue portfolio strategy, see Kearns (2007), Froelich (1999), and Chang and Tuckman (1994). 22 While Vermeer et al (2009a) report no statistical association between contributions and audit fees, Pearson et al (1998) report a negative association, and Beattie et al (2001) report a positive association.…”
mentioning
confidence: 99%
“…The distribution is illustrated in Figure 2. Consistent with research by Salamon (1987) and Chang and Tuckman (1994), over 90 percent of organizations have more than one funding source. Because we have no data on either proportion of funding from individual sources or exact dollar values, we are limited to using the count of sources as our dependent variable.…”
Section: Description Of the Stepwise Regressionsupporting
confidence: 74%
“…Foster and Bradach (2005) also found that between 1991 and 2001, earned income was concentrated in health and education organisations. After calculating a concentration index with a score of 1.0 representing complete concentration, Chang and Tuckman (1994) found that the mean concentration index of over 113,000 nonprofits in 26 activity categories ranged from 0.5 to 0.81, indicating that nonprofits tend towards more concentrated revenue. Activity categories with higher concentration indices include health, consumer protection and legal aid, and housing, while arts, environment, and animal-related activity categories had the lowest mean concentration indices of approximately 0.5.…”
Section: Which Organisations Are Adopting Mixed Revenue Strategies?mentioning
confidence: 99%